2008
DOI: 10.1029/2007wr006570
|View full text |Cite
|
Sign up to set email alerts
|

Coupled thermohydromechanical analysis of Venice lagoon salt marshes

Abstract: [1] A fully coupled thermohydromechanical (THM) finite element approach is used here to model the groundwater and saturation response of a typical salt marsh of the Venice lagoon (Italy) subjected to both tide fluctuation and flooding. The soil forming the marsh, whose relevant material parameters have been measured experimentally in the laboratory, is assumed to be an homogeneous multiphase porous medium, in a thermodynamic equilibrium state both in fully saturated and partially saturated conditions. More par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…Regarding (iii), since the presence of cracks is crucial in promoting bank retreat, their formation deserves more attention. Some authors proposed different mechanisms for their occurrence in marsh environment: desiccation processes across seasonal variation [ Allen , ; Morris et al ., ] and cyclic oscillation of mean and effective stresses due to tide [ Cola et al ., ]. Both mechanisms act at large time scale, and they involve filtration processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding (iii), since the presence of cracks is crucial in promoting bank retreat, their formation deserves more attention. Some authors proposed different mechanisms for their occurrence in marsh environment: desiccation processes across seasonal variation [ Allen , ; Morris et al ., ] and cyclic oscillation of mean and effective stresses due to tide [ Cola et al ., ]. Both mechanisms act at large time scale, and they involve filtration processes.…”
Section: Discussionmentioning
confidence: 99%
“…Tension cracks most frequently form at the end of the summer season due to the drying and shrinkage of the soil [ Allen , ; Morris et al ., ]; furthermore, Cola et al . [] hypothesized that the formation of tension cracks induced by the cyclic oscillation of mean and effective stresses is due to tidal wave fluctuation. Recent experimental results [ Francalanci et al ., ] have shown that toppling failure typology can occur during salt marsh retreat processes, especially under the effect of wind wave forcing, and can be triggered by the presence of tension cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Reported saturated hydraulic conductivity values similar to our 0.07-0.0007 m d À1 values include an Australian estuarine marsh, 0.01-0.17 m d À1 [Hughes et al, 1998], and a Venice lagoon marsh, 0.00017 m d À1 (core) and 0.086-0.00086 m d À1 (models) [Cola et al, 2008]. Regarding topography, the use of a kriged surface in the central portion of our models did not capture microtopographic variations in surface elevation that might affect very local hydraulics.…”
Section: Limitations Of the Modelsmentioning
confidence: 91%
“…[] for a detailed description of the study site). Shallower soils in the Venice Lagoon are characterized by sandy clay and silt successions [ Cola et al ., ]. The ERT application to the San Felice marsh is based on custom‐made waterproof micro‐ERT boreholes, acting in two microboreholes plus surface electrodes.…”
Section: Methodsmentioning
confidence: 99%